DETERMINANTS, PREVALENCE AND EFFECTS OF ELECTRICITY THEFT AMONG HOUSEHOLDS IN LAGOS STATE (2021)
Unstable electricity supply has been a major hindrance to economic development in Nigeria. Attainment of stable and reliable electricity supply requires three basic dimensions: technicalities, organisational structures and reduction of Electricity Theft (ET) to the barest minimum. Previous studies focussed more on the technical and organisational requirements with little attention paid to ET and its resultant effects particularly at household level. Therefore, this study was designed to examine the determinants of ET, its prevalence and effects among households in Lagos State, Nigeria. Becker’s Economic Theory of Criminal Behaviour served as the framework, while a survey design was adopted. A self-developed structured questionnaire focusing on determinants, prevalence and effects of ET was randomly administered to 580 household’s (area of franchise under Ikeja Electric Plc. (n = 330), and Eko Electricity Distribution Company (n= 250) electricity end-users in Lagos State. Bribery and Corruption (BC), Income Level (IL), Lack of Punishment of Earlier Offenders (LPEO), Running Micro-Business in Residential Apartments (RMBRA), Non Availability of Taskforce (NAT) to apprehend perpetrators, Frequency of Power Outages (FPO), Electricity Tariff (ELT) and Weak Enforcement of Anti-Electricity Theft laws (WEAET) were factors investigated as potential drivers of ET. Descriptive statistics were used to analyse prevalence and effects of ET, while Probit Regression estimation technique was used to identify its determinants among households at α0.05. The key drivers of ET were BC (β=0.063), IL (β= 0.060), LPEO (β=0.020), RMBRA (β=0.040), FPO (β=0.101), WEAET (β=0.104) and ELT (β=0.139). All the factors were positive and statistically significant. An important driver of ET, IL (β= 0.060), which was positive and statistically significant indicated that incidence of ET cuts across all income groups in Lagos State. The prevalence of electricity theft was (in two digits) 14.0% indicating excessive involvement of household electricity end-users in ET. The major effects of electricity theft included damage to electric power equipment (64.4%), difficulty in planning for service delivery (68.2%), increased expenses on self-power generation (51.6%), damage to household appliances (61.4%), epileptic electricity supply (72.4%), brown out (73.2%), poor revenue to the electricity distribution companies (82.0%) and further reduction in the quantity of electricity available for household use (72 .4%). The incidence of ET in Lagos State was widespread, cut across all income groups and had varied significant harmful effects on both the households’ electricity end-users and the electric power utilities. Strong determinants of Electricity Theft among households in Lagos State, Nigeria, were corruption, running micro business within residential apartments and weak enforcement of anti-electricity theft laws with severe consequences on the entire electric power value chain. Strengthening institutions for enforcement and application of anti-electricity theft laws is recommended to mitigate the problem.